Olesoxime Inhibits Cardioplegia-Induced Ischemia/Reperfusion Injury. A Study in Langendorff-Perfused Rabbit Hearts - Salameh, Aida; Keller, Maren; Dähnert, Ingo; Dhein, Stefan (Frontiers in Physiology, 2017)
Objective: During cardioplegia, which is often used in cardiac surgery, the heart is subjected to global ischemia/reperfusion injury, which can result in a post-operative impairment of cardiac function. Mitochondria permeability transition pores (MPTP) play a key role in cardiomyocyte survival after ischemia/reperfusion injury. It was shown in clinical settings that blockers of MPTP like cyclosporine might have a positive influence on cardiac function after cardioplegic arrest. Olesoxime, which is a new drug with MPTP blocking activity, has been introduced as a neuroprotective therapeutic agent. This drug has not been investigated on a possible positive effect in ischemia/reperfusion injury in hearts. Therefore, the aim of our study was to investigate possible effects of olesoxime on cardiac recovery after cardioplegic arrest. Methods: We evaluated 14 mature Chinchilla bastard rabbits of 1500-2000g. Rabbit hearts were isolated and perfused with constant pressure according to Langendorff. After induction of cardioplegic arrest (30ml 4°C cold Custodiol cardioplegia without and with 5µmol/L olesoxime, n=7 each) the hearts maintained arrested for 90-minutes. Thereafter, the hearts were re-perfused for 60 minutes. At the end of each experiment left ventricular samples were frozen in liquid nitrogen for ATP measurements. Furthermore, heart slices were embedded in paraffin for histological analysis. During the entire experiment hemodynamic and functional data such as left ventricular pressure (LVP), dp/dt(max) and (min), pressure rate product (PRP), coronary flow, pO2 and pCO2 were also assessed. Results: Histological analysis revealed that despite the same ischemic burden for both groups markers of nitrosative and oxidative stress were significantly lower in the olesoxime group. Moreover, hearts of the olesoxime-group showed a significantly faster and better hemodynamic recovery during reperfusion. In addition, tissue ATP-levels were significantly higher in the olesoxime treated hearts. Conclusions: Olesoxime significantly protected the cardiac muscle from ischemia/reperfusion injury.